2004
DOI: 10.1524/ract.92.12.903.55114
|View full text |Cite
|
Sign up to set email alerts
|

Uranium(VI) complexes with sugar phosphates in aqueous solution

Abstract: Uranium / Sugar phosphate / Complex formation / Potentiometric titration / TRLFS / EXAFSSummary. The complex formation in the aqueous systems of uranium(VI) with glucose 6-phosphate (G6P) and fructose 6-phosphate (F6P) were studied using potentiometric titration, TRLFS, and EXAFS. Two complexes with a uranyl-to-ligand ratio of 1 : 1 and 1 : 2 for both sugars were observed. Complex stability constants were determined by potentiometric titration for both complexes to be log β 11 (G6P) = 5.89 ± 0.40, log β 12 (G6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
24
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(30 citation statements)
references
References 31 publications
6
24
0
Order By: Relevance
“…The crystalline uranium phosphate formation following uranium accumulation indicates possible complexation of such metal with cellular phosphate groups facilitating metal nucleation and precipitation in a crystalline state [24]. Previous studies on molecular level speciation of uranium complexes within the cells of Stenotrophomonas maltophilia JG-2, M. oxydans SW-3 and Sphingomonas sp., isolated from uranium mill tailings by EXFAS revealed that at higher pH (pH 4.5) cell bound uranium biomineralize as U phosphate compounds [1,25]. The above observations not only indicate the role of bacterial PO 4 2− groups in uranium binding, but also illustrate the effect of pH on crystallinity of the cell bound U deposits.…”
Section: X-ray Powder Diffraction (Xrd) Analysismentioning
confidence: 69%
See 1 more Smart Citation
“…The crystalline uranium phosphate formation following uranium accumulation indicates possible complexation of such metal with cellular phosphate groups facilitating metal nucleation and precipitation in a crystalline state [24]. Previous studies on molecular level speciation of uranium complexes within the cells of Stenotrophomonas maltophilia JG-2, M. oxydans SW-3 and Sphingomonas sp., isolated from uranium mill tailings by EXFAS revealed that at higher pH (pH 4.5) cell bound uranium biomineralize as U phosphate compounds [1,25]. The above observations not only indicate the role of bacterial PO 4 2− groups in uranium binding, but also illustrate the effect of pH on crystallinity of the cell bound U deposits.…”
Section: X-ray Powder Diffraction (Xrd) Analysismentioning
confidence: 69%
“…In contrast to the amorphous nature of metal free biomass, spectrum for the uranium loaded cells showed distinct reproducible patterns typical for well characterized materials. The XRD pattern of the later biomass showed three distinct peaks at 2Â, 25 (Fig. 3c-e).…”
Section: X-ray Powder Diffraction (Xrd) Analysismentioning
confidence: 97%
“…In previous studies, the combination of EXAFS spectroscopy, TEM, and EDX analysis showed that phosphorus-containing residues of three ecotypes of A. ferrooxidans are involved in the complexation of uranium (40). In addition, the structural parameters of these uranium complexes appear similar to those arising from the complexation of uranium with organic phosphate compounds such as fructose 6-phosphate (28).…”
Section: Discussionmentioning
confidence: 91%
“…and Sphingomonas sp.) isolated from radioactive subsurface depository have demonstrated the complexation of uranium with cellular organic phosphate (fructose 6 phosphate) present at the cell surface at pH 2 (Koban et al 2004). Various cellular mechanisms employed by cyanobacterial strains for uranium detoxification including surface complexation by ligands harboured within the extracellular polysaccharides (EPS) have been reported (Acharya et al 2009;Acharya and Apte 2013a).…”
Section: Bioadsorptionmentioning
confidence: 99%